Analisis Permasalahan Pembelajaran IPS Di SD Negeri 105292 Bandar Klippa - Yun Parbueuli Munte; Reza Anggreini Br Milala; Syahrial (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research was conducted with the aim of finding out what obstacles teachers face in learning social studies at the State Elementary School 105292 Bandar Klippa. The type of research used is qualitative research. The researchers obtained the information by conducting interviews with one of the teachers at the elementary school. 105292 Bandar Klippa. After the researchers obtained some information, the researchers also conducted a literature study to obtain more information. The methods used were interviews and also literature studies, where literature studies are the process of reviewing several sources such as books, journals and reports. reports related to the topics discussed. As for the obstacles encountered in social studies learning at SDN 105292 Bandar Klippa, researchers found several problems related to curriculum implementation and learning planning, including inadequate facilities and infrastructure, teaching staff who have not yet mastered preparing a lesson plan. , too much material is given to students. In fact, many people think that some learning materials are too heavy for that age. Thus, the student's learning burden becomes increasingly large and heavy. Lack of book media to support independent curriculum-based learning activities